2007
DOI: 10.1038/sj.ki.5001940
|View full text |Cite
|
Sign up to set email alerts
|

Accepting prospective kidney donors with asymptomatic urinary abnormalities: Are we shooting in the dark?

Abstract: CASE PRESENTATIONA 53-year-old Caucasian lady was evaluated in our center as a potential kidney donor. She volunteered to donate a kidney to her brother with whom she shared a 6/6-antigen match. The exact etiology of her brother's end-stage renal disease (ESRD) could not be determined. On evaluation she was noted to be in good health and a review of systems was unremarkable. Family history was significant for functional pituitary tumor leading to acromegaly and diabetes in her father and renal cell carcinoma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The high 25.6% prevalence of occasional or persistent hematuria after donation means that hematuria is common in living kidney donation. Because extraglomerular bleeding can be excluded by evaluations such as computed tomography, sonography and urine cytology (20), isolated hematuria in pre-or postdonation donors is most likely to be of glomerular origin, suggesting the presence of glomerular diseases such as thin basement membrane nephropathy (TBMN), IgAN or AS, particularly if hematuria is dysmorphic. Although histological findings could not be evaluated in this study, we expect that light microscopy in many of the donors would have revealed minor glomerular abnormality, mild mesangial proliferative change, or partially global sclerosis in glomeruli, with either mesangial IgA and C3 deposition by immunofluorescence (IgAN), as well as thin glomerular basement membrane (GBM) and segmental attenuation of the lamina densa (TBMN), or thickening and lamellation of GBM (AS) on electron microscopy, as previously reported (19,20,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high 25.6% prevalence of occasional or persistent hematuria after donation means that hematuria is common in living kidney donation. Because extraglomerular bleeding can be excluded by evaluations such as computed tomography, sonography and urine cytology (20), isolated hematuria in pre-or postdonation donors is most likely to be of glomerular origin, suggesting the presence of glomerular diseases such as thin basement membrane nephropathy (TBMN), IgAN or AS, particularly if hematuria is dysmorphic. Although histological findings could not be evaluated in this study, we expect that light microscopy in many of the donors would have revealed minor glomerular abnormality, mild mesangial proliferative change, or partially global sclerosis in glomeruli, with either mesangial IgA and C3 deposition by immunofluorescence (IgAN), as well as thin glomerular basement membrane (GBM) and segmental attenuation of the lamina densa (TBMN), or thickening and lamellation of GBM (AS) on electron microscopy, as previously reported (19,20,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although the paucity of evidence for the eligibility of candidates with isolated hematuria and their risk after donation has meant that the acceptability of glomerular hematuria in kidney donors remains controversial (19,20,29,31,32), our results clearly show that donors with persistent hematuria and d-RBC are at significant risk of developing persistent proteinuria or lower GFR, which also confer worse renal outcomes in patients with TBMN, IgAN or AS (31,(33)(34)(35)(36). The eligibility of potential donors with isolated but persistent dysmorphic hematuria should therefore be closely considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, individuals who would have previously been deemed unsuitable as living donors due to relative medical contraindications are being considered. Described variably as having ‘isolated medical abnormalities (IMAs)’ (1,2), ‘asymptomatic urinary abnormalities’ (3) or as ‘complex’, ‘marginal’ or ‘at incremental risk’ (4–6), these living donors have conditions such as older age, obesity, hypertension, microscopic hematuria, proteinuria, reduced glomerular filtration rate (GFR) or nephrolithiasis (7). They may also have more than one abnormality.…”
Section: Introductionmentioning
confidence: 99%